Concise enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol via Co-catalyzed HKR of anti-(2SR, 3RS)-3-methoxy-3-phenyl-1, 2-epoxypropane - Kiran, I. N. Chaithanya; Reddy, R. Santhosh; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2011)
A short, enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol, cytotoxic styryllactones, has been achieved in high optical purities (99% ee). The strategy employs Co-catalyzed HKR of racemic anti-(2SR, 3RS)-3-methoxy-3-phenyl-1,2-epoxypropane and Lewis acid-mediated diastereoselective allylation of aldehyde as chiral inducing key reactions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Allylation; diastereoselectivity; Hydrolytic kinetic resolution; Racemic anti-epoxide; Styryllactones

CN-assisted oxidative cyclization of cyano cinnamates and styrene derivatives: a facile entry to 3-substituted chiral phthalides - Reddy, R. Santhosh; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2012)
The asymmetric dihydroxylation (AD) of o-cyano cinnamates and styrene derivatives leads to efficient construction of chiral phthalide frameworks in high optical purities. This unique reaction is characterized by unusual synergism between CN and osmate groups resulting in rate enhancement of the AD process. The method is amply demonstrated by the synthesis and the structural/stereochemical assignment of the natural products.

N-Heterocyclic carbene catalyzed esterification of aromatic aldehydes with alcohols under aerobic conditions - Kiran, I. N. Chaithanya; Lalwani, Komal G.; Sudalai, Arumugam (RSC Advances, 2013)
A simple, organocatalytic procedure for the direct oxidative esterification of a variety of aromatic aldehydes with alcohols has been described that affords the corresponding aromatic esters in high yields. The method employs N-heterocyclic carbenes as catalysts and molecular O-2 as an oxidant under ambient conditions.

Proline-catalyzed alpha-aminooxylation of beta-amino aldehydes: access to enantiomerically pure syn- and anti-3-amino-3-aryl-1,2-alkanediols - Venkataramasubramanian, V.; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Synlett, 2015)
A new synthetic method for enantioselective synthesis of syn 3-amino-3-aryl-1,2-alkanediols via praline catalyzed alpha-aminaoxn y ylation of beta-amino aldehydes des are described. This methodology is successfully applied to a concise and protecting group-free asymmetric synthesis of (-)-cytoxazone (+)-epi-cytoxazone and formal synthesis of N-thiolated 2-oxazolidinone.
Keywords: amino aldehydes; Asymmetric synthesis; catalysis; diastereoselectivity; Enantioselectivity; Natural product